The Impact of Globalization on Traditional Foodways in Palembang, Indonesia - Mutiara, Sinthya; Muhammad Hasan (Enigma in Cultural, 2024)
Globalization has profoundly influenced cultures worldwide, impacting even the most intimate aspects of daily life, such as food. This research explores the effects of globalization on traditional foodways in Palembang City, Indonesia, examining changes in food consumption patterns, preparation methods, and the socio-cultural significance of food. This study utilized a mixed-method approach. A survey was conducted with 200 residents of Palembang City to assess changes in food consumption patterns and attitudes toward traditional food. Semi-structured interviews were conducted with 15 local food vendors and culinary experts to gain in-depth insights into the challenges and adaptations in food preparation and the cultural implications of these changes. The findings indicate a discernible shift in food consumption patterns towards more convenient, processed, and globalized food options. Traditional food preparation methods are being simplified or replaced with modern techniques, and the socio-cultural significance of food is undergoing transformations. Globalization has undeniably impacted traditional foodways in Palembang City. While adaptation and change are inevitable, efforts must be made to preserve and promote traditional foodways to maintain cultural identity and culinary heritage.